Imaginativeness and motivation of a symbol (Eurasian Journal of Philology Science and Education, 2015)
The main object of our research, symbol, not fully defined in linguistic literature. There are a lot of work done in other areas of study such as philosophy, semiotics, psychology, philology, mythopoeic and folkloristic. We try to system the main points of view in order to show all characteristics of this many-sided phenomenon and reveal studying of it with the help of linguistic means and especially structural semantics. In humanitarian tradition symbol has many characteristicssuch as imaginativeness, motivation, combined content of symbol and its meaning’s equality, immanentive polysemy and vagueness of limits of meaning in symbol, archetypical symbol, its universality in separately taken culture and a recross of symbols in cultures of different times and people, symbol in structure of mythology, literature, art and other semiotics systems; besides, the relation of symbolical to language reality and place of symbol in language and speech was studied. In this article we consider – imaginativeness and motivation of asymbol.
Keywords: symbol; semiotic definition; imaginativeness; motiveness; abstract; metaphor; metonymy; synecdoche.